The Correlation Cervical Radiograph in ThreeImages Position With Clinical Symptoms of Cervical Syndrome - Ana Majdawati (Fakultas Kedokteran Universitas Jenderal Soedirman, 2020)
Cervical Syndrome is a complaint of pain in the cervical vertebrae area, which has the most number 2 after complaints of low back pain (LBP). 3-position cervical radiographic examination is a diagnostic investigation which is still frequently proposed in cervical syndrome cases. The formulation of the problem in this study is there a relationship between cervical 3 position radiography and clinical symptoms of Cervical Syndrome? This research method is cross sectional to obtain cervical radiolographic relationship which includes osteophytes, DIV/FIV narrowing, subchondral sclerotic, fracture/compression, listhesis, calcification of anterior/posterior cervical ligament with clinical symptoms of Cervical Syndrome patients ie neck stiffness, neck/neck pain, fractures/compressions, listhesis, calcification of anterior / posterior cervicalis ligaments with clinical symptoms of Cervical Syndrome patients ie neck stiffness, neck / neck pain, fractures/compressions, listhesis, calcification of anterior/posterior cervicalis ligaments with clinical symptoms of Cervical Syndrome patients ie neck stiffness, neck/neck pain, propagation, compression pain to the shoulder, back of the head and arms, movement disorders and paresthese. The data obtained were tested by chi square analysis with p = 0.036. The results of this study show a significant relationship between clinical symptoms of cervical syndrome with cervical 3 position radiographic results.